Educational Activity in Islamic Education: Evaluation of Hadith Course for First Intermediate Grade in Kingdom of Saudi Arabia - Salem Ali Al-Qahtani; Asyraf Isyraqi Jamil; Fakhrul Adabi Abdul Kadir (AT-TA'LIM, 2018)
The objective of this research is to determine how far the general objectives of teaching the subject of Hadith for the first intermediate grade have been achieved. The main question of this study is how adequate the educational activities in achieving the general objectives of teaching the subject of Hadith for the first intermediate grade. The study has used analytical descriptive approach to answer the questions of research. The tool of research is an analysis card which contains 52 educational activities; the sample of research. The study came to results which are: 1) the criteria laid down for the study were highly verified and the average was (3.50), 2) achieving the axis of the study that represented the tool was arranged by the criteria related to the form of knowledge which highly verified and the average was (3.87) and the criteria related to the general objectives of teaching the subject of Hadith which highly verified and the average was (3.43), and 3) The criteria related to the activities and their general ways were highly verified and the average was (3.13). Some of the most important recommendations of the study are to increase the quorum of Hadith to two classes per week, to care of educating students about the concept of activity and the difference between it and the content and the benefit of each of them to students, in a language that can be understood simply by the students, to differentiate between activities of male students and female students after uniting the content which is better that the activities become to each sex according to what is suitable to nature and characteristic, and to form special committees or appointing educational supervisors whose first task is to follow up educational activities in the Islamic religious courses, and evaluating them, and then help the teacher and students to pass everything can be difficult to achieve these activities.